Metabolism of 4-methylimidazole in Fischer 344 rats and B6C3F1 mice. (January 2019) - Fennell, Timothy R.; Watson, Scott L.; Dhungana, Suraj; Snyder, Rodney W.
Abstract: 4-Methylimidazole (4-MeI) is a widely used chemical, also identified as a by-product of heating foods. In cancer bioassays, 4-MeI induced lung tumors in mice, but not in rats. To establish if metabolic differences could explain species difference in carcinogenicity, this study investigated metabolism of 4-MeI in rat and mouse lung and liver microsomes and S-9 fractions, and in vivo in rats and mice. No metabolites were detected in rat or mouse lung and liver microsomes, or lung S-9 fractions. Male and female F-344 rats and B6C3F1 mice were administered 50 and 150 mg/kg [ 14 C] 4-MeI by gavage. Excreta, exhaled CO2 and volatiles were collected for 48 h. Elimination was mainly via urine, with 79–89% of the radioactivity in urine in rats and 41–70% in mice. Most of the radioactivity (71–88%) in urine was unchanged 4-MeI. Additional radioactive peaks (the largest metabolite was 8–18%) were characterized by LC-MS/MS as 4-hydroxymethylimidazole, its glucuronide, and other oxidized products, including methylhydantoin. 4-MeI was largely excreted unchanged in rats and mice with limited oxidative metabolism and conjugation. 4-MeI was not oxidized in subcellular fractions from rat and mouse lung and liver. Overall, the metabolism of 4-MeI appeared similar between rats and mice. Highlights: 4-Methylimidazole was not metabolized in vitro in microsomes or S-9 from rat and mouse liver and lung. 4-Methylimidazole was rapidly eliminated after gavage administration in vivo in rats and mice. 4-Methylimidazole was excreted in urine largely unchanged and after metabolism by hydroxylation and glucuronidation.